Inhibition and kinetic studies of lignin degrading enzymes of Ganoderma boninense by naturally occurring phenolic compounds - A., Surendran; Y., Siddiqui; H. M., Saud; N. S., Ali; S., Manickam (Wiley, 2018)
Aim Lignolytic (lignin degrading) enzyme, from oil palm pathogen Ganoderma boninense Pat. (Syn G. orbiforme (Ryvarden)), is involved in the detoxification and the degradation of lignin in the oil palm and is the rate‐limiting step in the infection process of this fungus. Active inhibition of lignin‐degrading enzymes secreted by G. boninense by various naturally occurring phenolic compounds and estimation of efficiency on pathogen suppression was aimed at.